Pengaruh model pembelajaran Li-Pro-GP terhadap kemampuan berpikir kreatif dan kemampuan komunikasi tulisan pada pembelajaran IPA biologi SMP - Savitri, Aulia; Pantiwati, Yuni; Fauzi, Ahmad; Wahyuni, Sri; Permana, Tutut Indria (Universitas Negeri Jakarta, 2025)
Students' creativity and written communication are essential 21st-century skills, yet junior high school students often show low abilities in these areas due to passive, monotonous learning and limited writing practice. This study investigates the effect of the Li-Pro-GP learning model a project-based literacy approach integrated with the School Literacy Movement (SLM) and Strengthening Character Education (SCE) on improving students' creative thinking and written communication abilities. This study used a quantitative approach with a quasi-experimental non-equivalent control group design. The sampling technique used was purposive sampling based on equal number of students and gender balance. VIII F served as the experimental class and VIII G as the control class, each consisting of 34 students with 15 males and 19 females. The research instrument used to measure creative thinking ability and written communication ability is an essay question each designed with distinct indicatiors. Creative thinking instruments emphasize innovative ideas and solutions, while written communication instruments emphasize clarity, structure, and accuracy in expressing ideas. The data were analyzed using ANCOVA and Quade's Rank Analysis with the help of SPSS 27 and JASP applications. The results of the analysis showed that the Li-Pro-GP model had a significant effect on creative thinking ability with a value of F (1,65) = 32.644, p < 0.001 and written communication ability with a value of F (1,66) = 47.259, p < 0.001. In conclusion, the application of the Li-Pro-GP learning model has an effect in improving the creative thinking and written communication ability of junior high school students.